Analysis of Vitamin A Content and Antioxidant Test in Super and Bulk Olein - Saputri, Desi Riana; Listyadevi, Yuniar Luthfia; Putra, Muhammad Alparidi Pamungkas; Adiwibowo, Muhammad Triyogo; Sanjaya, Andri; Damayanti, Damayanti; Auriyani, Wika Atro; Fahni, Yunita; Yusupandi, Fauzi; Yuniarti, Reni; Safitra, Edwin Rizki (Communication in Food Science and Technology, 2024)
Cooking oil is the essential food for bodies. Cooking oil should be enriched with vitamin A because this substance plays a critical role in maintaining health. Cooking oil contains antioxidant compounds, which inhibit or slow down oxidation reactions. This study aimed to determine the amount of vitamin A in super olein and bulk olein before fortification and the amount of antioxidant content in super olein and bulk olein before fortification. The amount of vitamin A content was obtained using the High-Performance Liquid Chromatography (HPLC) method of <0.005 IU/gram, while the antioxidant test results were carried out by the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) method using UltraViolet-Visible Spectrophotometry (UV-Vis). The resulting antioxidant activity has an inhibition value of 23% and 10% in bulk and super olein, respectively. Cooking oil is the essential food for bodies. Cooking oil should be enriched with vitamin A because this substance plays a critical role in maintaining health. Cooking oil contains antioxidant compounds, which inhibit or slow down oxidation reactions. This study aimed to determine the amount of vitamin A in super olein and bulk olein before fortification and the amount of antioxidant content in super olein and bulk olein before fortification. The amount of vitamin A content was obtained using the High-Performance Liquid Chromatography (HPLC) method of <0.005 IU/gram, while the antioxidant test results were carried out by the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) method using UltraViolet-Visible Spectrophotometry (UV-Vis). The resulting antioxidant activity has an inhibition value of 23% and 10% in bulk and super olein, respectively.